Antibacterial action of the phytosubstances from Ledum palustre shoots - Tolmachova К; Kireyev І; Osolodchenko, T; Koshovyi, O; Upyr Т (Annals of Mechnikov’s Institute, 2019)
The aim of the research isto study the antibacterial activity of phytosubstances from Ledum palustreshoots. Materials and Methods. The study objects were 8 phytosubstances from Ledum palustreshoots. The study of the antibacterial activity of phytosubstances with Ledum palustre was performed at the premises of Mechnikov Institute ofMicrobiology and Immunology of the NAMS of Ukraine in the Laboratory of Biochemistry and Biotechnology under the supervision of the head of the Laboratory, Candidate of Biology (Ph.D.)Osolodchenko T. P.Results. The study has shown that phytosubstancesfrom Ledum palustreshoots exhibit the antibacterial action against pathogens of respiratory tract diseases, namely Moraxella catarrhalis, Haemophilus influenzae, Streptococcus pneumoniae, Staphylococcus aureus, Klebsiella pneumoniae. According to the results of the study, phytosubstances, which in their composition have terpene compounds, have antibacterial effects in relation to Klebsiella pneumoniaeand Staphylococcus aureus. Meanwhile, the Ledum palustre phenol complex exhibits a pronounced antibacterial effect toHaemophilus influenzae andStreptococcus pneumoniae, also medium antibacterial effectin relation to Moraxella catarrhalis.